HUBUNGAN ASUPAN KALSIUM,VITAMIN D, FOSFOR, KAFEIN, AKTIVITAS FISIK DENGAN KEPADATAN TULANG PADA WANITA DEWASA MUDA (Studi Kasus pada Mahasiswi S1 Reguler Fakultas Kesehatan Masyarakat Universitas Diponegoro Angkatan 2014) - Fitri Khoiriyah P.; M. Zen Rahfiludin; Siti Fatimah Pradigdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Bone density is a bone mass in our body that shows bone compactness. Bones that we do not keep early can cause abrasion. The occurrence of bone loss even to the osteoporosis can be influenced by factors that can not be changed as well as factors that can be changed. The purpose of this research is to know the relationship between calcium, phosphorus, vitamin D intake, caffeine, and physical activity with bone density of young adult women in Regular S1 student of Faculty of Public Health Diponegoro University 2014. This research is an analytical quantitative research with cross sectional study design. Population in this research is student of Faculty of Public Health Diponegoro University force of 2014 number of 300 student which then taken sample counted 75 student with random sampling technique. Data were collected using FFQ-Semi Quantitative form, physical activity recall form PAL (Physical Activity Level), Scale measurement of bone density and analyzed using Chi Square test. The results showed that calcium and vitamin D intake classified as less (78.7% and 100%), whereas phosphorus intake was good (54.7%). Physical activity is very low (61,3%), and frequent caffeine consumption (50.7%). The results showed no association between calcium, vitamin D, phosphorus intake and physical activity with bone density (p Value> 0.05), but there was a relationship between the frequency of caffeine consumption and bone density in young adult women (p Value = 0.028). This study recommends young adult women especially college students to be able to re-adjust the intake of nutrients consumed, in addition to the need for regular physical activity in order to maintain bone density early on.